Biodiversity of floristic complexes on the territory of the Ketpen-Temerlik range (Experimental biology, 2019)
The article provides an analysis of the biodiversity of the floristic complexes of the Ketpen-Temerlik range within Kazakhstan and China. According to the results of perennial floristic studies in the territory of the Ketpen-Temerlik range within Kazakhstan and China, there are 1,890 species of vascular plants belonging to 593 genera and 120 families. In terms of species composition, the Magnoliophyta section dominates in the study area of the Ketpen-Temerlik range, which accounts for 98.4% and 1.6% for Pinophyta, Polypodiophyta, Lycopodiophyta, and Equisetophyta. The ratio of monocotyledonous and dicotyledonous groups in the flora of the ridge is approximately 1: 5.4, where Magnoliopsida prevails over Liliopsida by species and genus composition more than 5 times. The total number of dicotyledonous plants is 1,510 species, which is 80%, monocotyledonous plants are only 350 species. We have identified 13 floristic complexes for the Ketpen-Temerlik range: desert, desert-steppe, meadow, meadow-forest, deciduous-forest, coniferous-forest, cryophilic-meadow, steppe, tree-shrub, petrophilic, wetland and coastal-water and synanthropic. Their isolation as floristic complexes is quite natural, since they are zonal for the studied territory, the vegetation cover of which is distinguished by complexity and mosaic. Dominant on the Ketpen-Temerlik range are meadow-forest, steppe, co- ISSN 1563-0218; eISSN 2617-7498 Experimental Biology. №1 (78). 2019 47 Садырова Г.А. nifer-forest, cryophilic-meadow, petrophilic, woody shrub, gypsum-gammad and variegated floristic (landscape-geographical) complexes. Key words: biodiversity, flora, Ketpen range, Temerlik, floristic complexes